Complement analysis in the era of targeted therapeutics. (October 2018) - Prohászka, Zoltán; Kirschfink, Michael; Frazer-Abel, Ashley
Highlights: Complement testing is resurgent. Methods and need has expanded. It is important to understand the difference and limitations. Abstract: Complement immunobiology, and with it complement analysis, has undergone a renaissance in the past decade. Classically, complement analysis was limited number of testing C3, C4 in a routine laboratory with the possible addition of CH50 with all other analysis being performed at only few highly esoteric laboratories. This diagnostics expanding beyond specialized laboratories is the result of the growing recognition of the role played by complement dysfunction in many more diseases and disorders and the concomitant increase in interest in complement targeting therapeutics. In response, laboratories specializing in complement analysis have joined with the International Complement Society and the IUIS to coordinate efforts to standardize and improve complement testing, ongoing efforts that have already borne fruit. A recognition of the power of complement analysis has brought forward new testing but also realization of the importance of post-draw specimen handling to limit ex vivo activation, as well as the sometimes large difference between testing laboratory results. The increased usefulness of complement analysis and efforts to standardize and expand it means the future is strong for complement analysis.